OSTEOPOROSIS - STATISTICAL DATA FOR PATIENTS WITH OSTEOPOROSIS IN THE PERIOD FROM 2020 AND THE CURRENT 2021 - Zhu, Jihe; Arsovska, Blagica; Kozovska, Kristina (International Journal of Research -GRANTHAALAYAH, 2021)
About 120.000 women in Macedonia suffer from osteoporosis. These statistics of the World Health Organization are just a warning about the need for treatment and prevention of this disease. For this research were analyzed statistical data for patients with osteoporosis in the period from 2020 and the current 2021. The data were taken from PHI Medika - Strumica, R.N. Macedonia and the Faculty of Medicine, Skopje RS Macedonia. From the obtained data from 2020 and 2021 for the number of examinations that have been performed in patients with osteoporosis over 50 years, in 2020, out of a total of 542 examinations, 523 are women diagnosed with osteoporosis and 19 are men. In the current 2021, out of a total of 115 examinations, 112 are women and 3 men are registered with osteoporosis. From the obtained data from the PHI Medika - Strumica, in 2020, out of a total of 792 examinations, 762 are women diagnosed with osteoporosis and 30 are men. In the current 2021, out of a total of 256 examinations, 250 are women and 6 men. In women osteoporosis is significantly more common than in men. From the hospitalized patients with hip fracture because of osteoporosis, 3.4% of those who are hospitalized are patients aged from 60 to 69 years, 30.6% are aged from 70 to 79 years, 66% are patients aged 80+ years. Age also plays an important role in osteoporosis and fractures. Older people are more likely to need hospital care than younger people.